Numerical and Experimental Verification of a 3D Quasi-Optical System. (24th May 2015) - Lu, Zejian; Liu, Xiaoming; Wang, Hai; Chen, Xiaodong; Yao, Yuan; Yu, Junsheng
Abstract : A modular and efficient Gaussian beam (GB) analysis method, incorporating frame-based Gabor transformation, GB reflection, and a 3D GB diffraction technique, was developed to analyze both the reflectors and frequency selective surface (FSS) in quasi-optical (QO) system. To validate this analysis method, a 3D dual-channel QO system operating at 183 and 325 GHz was designed and tested. The proposed QO system employs two-layer structure with a FSS of perforated hexagonal array transmitting the 325 GHz signal on the top layer while diverting the 183 GHz signal to the bottom layer. Measured results of the system demonstrate that the agreement can be achieved down to −30 dB signal level for both channels in the far field pattern. The discrepancy between the calculation and measurement is within 2 dB in the main beam region (2.5 times −3 dB beamwidth), verifying the effectiveness and accuracy of the proposed method.